Identification and Validation of Feature Genes Related to Mitochondrial Dysfunction and Oxidative Stress in Ulcerative Colitis - Wu Y; Tan Z; Lan Q; Liu Y; Liu C; He H; Zhang J; Dong W (Journal of Inflammation Research)
Yanrui Wu,1,* Zongbiao Tan,1,* Qingzhi Lan,2,* Yupei Liu,1 Chuan Liu,1 Haodong He,1 Jixiang Zhang,1 Weiguo Dong1 1Department of Gastroenterology, Renmin Hospital of Wuhan University, Wuhan, People’s Republic of China; 2Department of Pathology, Renmin Hospital of Wuhan University, Wuhan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Weiguo Dong, Department of Gastroenterology, Renmin Hospital of Wuhan University, 99 Zhangzhidong Road, Wuhan, Hubei Province, 430060, People’s Republic of China, Email dongweiguo@whu.edu.cnBackground: The roles of mitochondrial dysfunction (MD) and oxidative stress (OS) in the pathogenesis of ulcerative colitis (UC) have received increasing attention. Given their close association, it is crucial to clarify the molecular characteristics and biological functions of MD and OS-related genes in UC.Methods: Gene expression profiles, mitochondrial-related genes, and OS-related genes were obtained from the corresponding databases. Unsupervised clustering of UC samples was performed based on differentially expressed MD and OS-related genes (DEMORGs). The CIBERSORT algorithm was used to assess immune cell infiltration. Feature genes were selected from DEMORGs by machine learning. The receiver operating characteristic (ROC) curves were plotted, and a nomogram was constructed to evaluate the diagnostic efficacy of feature genes for UC. Colonoscopic biopsy tissues from UC patients and controls were collected retrospectively to verify the protein expression levels of feature genes through immunohistochemical staining.Results: Based on nine DEMORGs, two MD and OS-related subtypes were identified in UC samples. Subtype C2 is characterized by a more severe degree of MD, higher OS levels, and more severe disease activity. The infiltration proportions of follicular helper T cells, M1 macrophages, activated dendritic cells, and neutrophils were significantly higher in subtype C2 compared to subtype C1. CPT1A, EPHX2, and PRDX4 were obtained as UC feature genes related to MD and OS. All the three feature genes exhibited good diagnostic value for UC, and their expression levels were significantly correlated with the clinical activity of UC.Conclusion: CPT1A, EPHX2, and PRDX4 are feature genes related to MD and OS in UC, and their expression levels are significantly associated with the proportion of immune cell infiltration and disease activity. This study provides valuable insights into the role of MD and OS in UC.Keywords: ulcerative colitis, mitochondrial dysfunction, oxidative stress, bioinformatics analysis, machine learning